Hubungan Pengetahuan Dan Sikap Siswa Dengan Perilaku Pemilahan Sampah Di Smpn Kecamatan Bekasi Timur - Milawati Anbarsari; Nur Asiah; Awaluddin Hidayat Ramli Inaku (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Waste segregation is an activity in handling waste by classifying waste according to the type originating from the source. Implementation of waste sorting activities later so that every school member does not dispose of garbage in the same container. However, there are still many students who have not disposed of trash according to their type, even though the school has provided organic, non-organic, hazardous and toxic (B3) waste bins in every corner of the school yard. The purpose of this study was to determine the relationship between knowledge and attitudes with waste sorting behavior at SMPN 18 Bekasi Timur District. This study used a cross sectional approach. The population and sample of this study were all students of class VII at SMPN 18 Bekasi Timur District with 420 students, the sample in this study were 120 students. The data source used is primary data with data collection methods in the form of interviews with a questionnaire instrument. The results of this study found that the knowledge of students at SMPN 18 Bekasi Timur District was in the low category of 53.3%, had a negative attitude of 55.8%, had good behavior in sorting waste 68.3% and the availability of facilities was inadequate for 71.7%. Bivariate analysis showed that there was no relationship between knowledge and waste sorting behavior (Pvalue 0.536), there was a relationship between attitude and waste sorting behavior (Pvalue 0.006) and there was no relationship between the availability of facilities and waste sorting behavior (Pvalue 0.075%). It is recommended that schools provide education about environmental health, especially the waste management program.